Characterization of different types of anxiety disorders according to level of personality functioning and self-reported adverse and positive childhood experiences in a sample of psychotherapy outpatients [analysis] - Nowak, Jonathan; Dönnhoff, Ivo; Kindermann, David; Nikendei, Christoph (Universität, 2023)
This dataset contains the code for the analysis in R which was used to calculate the results for the study 'Characterization of different types of ...